The Role of Principal Leadership in Creating an Effective School Culture - Murtanti, Wilin; Satori, Djam'an; Nurdin, Diding; Kurniatun, Taufani Chusnul (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2024)
This study examines the critical role of principal leadership in fostering an effective school culture at SMA Negeri X in South Jakarta. Using a qualitative approach, data were collected through interviews, participant observations, and document analysis. The findings highlight the principal's adoption of a democratic and transformative leadership style, focusing on collaboration among stakeholders, establishing a clear vision, and promoting teacher and student development. Key strategies include fostering harmonious relationships, ensuring a safe and conducive school environment, implementing discipline, and nurturing a competitive and religious culture. The principal's leadership practices have significantly contributed to a positive school climate, characterized by improved student academic performance, strong teacher engagement, and active community involvement. These findings emphasize the pivotal role of visionary and participative leadership in building a robust educational culture. While the study is limited to one institution, it provides a foundation for further research into the relationship between leadership styles and school culture across diverse educational contexts.